Higher thermostability of L-lactate dehydrogenases is a key factor in decreasing the optical purity of D-lactic acid produced from Lactobacillus coryniformis - Gu, Sol-A.; Jun, Chanha; Joo, Jeong Chan; Kim, Seil; Lee, Seung Hwan; Kim, Yong Hwan (ELSEVIER SCIENCE INC, 2014)
Lactobacillus coryniformis is known to produce D-lactic acid as a dominant fermentation product at a cultivation temperature of approximately 30 degrees C. However, the considerable production of L-lactic acid is observed when the fermentation temperature is greater than 40 degrees C. Because optically pure lactates are synthesized from pyruvate by the catalysis of chiral-specific D- or L-lactate dehydrogenase, the higher thermostability of L-LDHs is assumed to be one of the key factors decreasing the optical purity of D-lactic acid produced from L. coryniformis at high temperature. To verify this hypothesis, two types of d-ldh genes and six types of l-ldh genes based on the genomic information of L. coryniformis were synthesized and expressed in Escherichia coll. Among the LDHs tested, five LDHs showed activity and were used to construct polyclonal antibodies. D-LDH1, L-LDH2, and L-LDH3 were found to be expressed in L. coryniformis by Western blotting analysis. The half-life values (t(1/2)) of the LDHs at 40 degrees C were estimated to be 10.50, 41.76, and 2311 min, and the T-50(10) values were 39.50,39.90, and 58.60 degrees C, respectively. In addition, the T-m values were 36.0, 41.0, and 62.4 degrees C, respectively, which indicates that L-LDH has greater thermostability than D-LDH. The higher thermostability of L-LDHs compared with that of D-LDH1 may be a major reason why the enantiopurity of n-lactic acid is decreased at high fermentation temperatures. The key enzymes characterized will suggest a direction for the design of genetically modified lactic acid bacteria to produce optically pure D-lactic acid. (c) 2014 Elsevier Inc. All rights reserved.